Audit Risk Assessment in the National Audit Office of the Republic of Lithuania: Evaluation and Development - Mackevičius, Jonas; Pranckevičiūtė, Laura (Ekonomika, 2004)
The article deals with audit risk assessment in the National Audit Office of the Republic of Lithuania (hereinafter referred to as the NAOL). The audit risk features, classification, elements and the place of audit risk assessment are outlined. The text includes the legitimate environment of audit risk assessment in the NAOL and the evaluation of the NAOL Financial Audit Assurance Model. The Public Institutions Financial Audit Manuals of the United Kingdom and Sweden are taken into consideration. As a result of the survey; the NAOL Financial Audit Risk Assessment Guide is recommended. The principal conceptions dealt with in the article: audit risk and its assessment, Financial Audit Assurance Model, Financial Audit Risk Assessment Guide, classification, elements, the National Audit Office of the Republic of Lithuania.